To Study the Safety of Multi-dose Topical Anaesthetic Eye Drops One Month after Opening - Muhammad Wasif Irshad, Mehr-un-Nisa Irfan Qayyum Malik (Pakistan Journal of Ophthalmology, 2019)
Purpose: To determine the risk of ocular infections due to topical multi-dose anaesthetic eye drops in patients one month after opening the bottle. Study Design: Quasi experimental study. Place and duration of study: Department of Ophthalmology DHQ Teaching Hospital, Gujranwala from 22nd May 2018 to 22nd June 2018. Materials and Methods: In this study topical anaesthetic eye drops containing proparacaine hydrochloride 0.5% as main ingredient and benzalkonium choride as preservative (Alcaine?) were tested daily to see if any bacterial/fungal growth occurs in the bottle containing eye drops or not. Same bottle was used in patients presenting in outdoor and indoor departments. Samples taken from the bottle contents were cultured on different media to see growth of fungi or bacteria. Patients who already had keratitis, conjunctivitis, corneal opacities, thin corneas and having dry eyes which were prone to get infected were excluded from this study. Results: There were 60 patients included in our study and they were divided in two groups. Group A included those who presented in the outdoor department and group B comprised of those admitted for various operative procedures. There were 30 patients in each group. All patients were adults (18-60 years). After 1 month of daily culturing on agar plates, no micro-organism growth was seen in both groups. Conclusion: Topical anaesthetic eye drops can be used safely for 1 month in different patients after opening the bottle without any risk of causing infectious keratitis, conjunctivitis or endophthalmitis. Keywords: Proparacaine, Culture medium, Endophthalmitis.